The specialty of the contract of participation that ended with ownership - عبد الصاحب, علي مطشر; هوبي, سرى محمد (Journal of Legal Sciences, 2019)
The contract of participation ended with ownership is considered as a new contract which preceded the legislations and accompanying the reality in which the parties of contract go into partnership in a certain project and sharing its profit and loss where any party shall own the project through buying the portion of the other party or parties from the incomes of that project or any other resources as a single payment or in form of payments as agreed.This type of contract has special provisions that made us to choose the specialty of contract of participation that ended with ownership as a subject to be discussed in this research through three research works:• The specialty of the concept of contract of participation that ended with ownership.• Forms of contract of participation that ended with ownership.• The specialty of the effects of contract of participation that ended with ownership.